Thomas Percy - Levinson, E; Carver, DC (Oxford University Press, 2021)
Thomas Percy (b. 1729–d. 1811) is primarily remembered for his seminal collection of ballads, Reliques of Ancient English Poetry. However, the 1765 publication of this text was only the midpoint of an extraordinarily prolific decade. After publishing some original poems and a translation of Ovid’s elegy for Tibullus in the 1750s, the 1760s also saw Percy produce the first Chinese novel translated into English, Hau Kiou Choaan (1761); Miscellaneous Pieces Relating to the Chinese (1762); The Matrons (1762); Five Pieces of Runic Poetry (1763); a new translation of The Song of Solomon (1764); A Key to the New Testament (1766); and his influential study of “Gothic” art and society, Northern Antiquities (1770). He also worked on his long poem, The Hermit of Warkworth (1771), and edited the Northumberland Houshold [sic] Book (1770). This only covers his published works: during the same period, he worked on several other editing and translating projects—preparing an edition of The Spectator and other journals by Addison and Steele, for example—which never reached print. As Percy rose through the ranks of the Anglican clergy—becoming one of the king’s chaplains by 1770, Dean of Carlisle in 1778, and finally Bishop of Dromore in 1782—he stopped publishing new works, perhaps because he thought it detracted from the dignity of his ecclesiastical office. Nevertheless, his translations of Spanish ballads—Ancient Songs, Chiefly on Moorish Subjects—were ready for press in 1775 (though they were only published in 1932). His extensive correspondence also reveals his continuing interest in literary matters, and he was certainly ready to lend a hand to other scholars, providing they were sufficiently polite. In antiquarian circles, Reliques of Ancient English Poetry attracted considerable attention: his theory of minstrels’ high status was disputed, and his editorial practice was (and remains) controversial. The literary reception was more positive. Although Percy’s own ballad, The Hermit of Warkworth, was mercilessly parodied by Samuel Johnson, the medieval ballads he anthologized were profoundly important to Romanticism, both British and German. As critics increasingly attend to Percy’s work beyond Reliques of Ancient English Poetry, other aspects of his influence—including troubling legacies—have come to light. His work on Spanish and Chinese material has been taken as foundational for “world literature,” and scholars have debated whether Percy’s treatment of China is orientalist, or whether there are ethnonationalist and racialist elements to Percy’s Gothic interests.